Empirical Application of Expenditure Diary Instrument to Quantify Relationships between In-Store and Online Grocery Shopping: Case Study of Greater London. Issue 1 (January 2015) - Suel, Esra; Le Vine, Scott; Polak, John
There is a sustained shift of certain types of retail activity away from in-store shopping and toward online retailing, with potentially structural consequences for shopping-related mobility. In the United Kingdom, for instance, 5.1% of spending on groceries in 2013 was transacted online, an increase from 3.8% in 2010. (The level was 1.1% in 2003.) Transport researchers face serious gaps in empirical data coverage of this phenomenon, however, because regional and national travel surveys typically collect limited information with which to establish how in-store and online shopping relate to one another. To address this issue, the authors employed a well-established data resource in a novel approach. The UK Living Costs and Food Survey is traditionally used to track aggregate household expenditure patterns and to monitor price inflation. This study drew on the unique nature of the survey's expenditure diary, in which respondents recorded each item that they purchased during a 2-week period; respondents also recorded whether each shopping occasion was in-store or online. Empirically, it was found that shopping basket characteristics (types of products being purchased) were significantly linked with channel choice (online versus in-store). Furthermore, with a two-stage modeling approach, it was found that sociodemographic factors appeared to relate in different ways to adoption of online shopping in general and to the choice of online versus in-store for individual shopping occasions. The paper closes with a brief discussion of research needs to advance this line of inquiry.